Kriteria Yang Berpengaruh Dalam Penilaian Kinerja Karyawan Menggunakan Anaytical Hierarchy Process - Hariyanto, Krisnadhi; Satoto, Eko Budi (Universitas Muhammadiyah Surakarta, 2016)
Employee performance is the result of work that is achieved or the results that have been done or worked by an employee within the chores that are charged to the employee. The problem is a priority weighting of the factors and sub factors to get the solution in advance in accordance with the order of priority. In this study the data collected is done by direct observation, interviews, questionnaires and literature. The data are processed to determine the priority weight of the components that affect employee performance. From the calculation by AHP method can be obtained by order of priority as follows: The first is the human resources with priority weight 0.558. The second is working environmental conditions with priority weight 0.312. Last is managerial with priority weight 0.131. Thus the factors that require attention and consideration of the company to increase work performance is a factor of human resource with the greatest priority weight.